2020
DOI: 10.1088/1755-1315/542/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of size reduction by batch ball milling process for crab shell powder prior hydroxyapatite conversion

Abstract: The crab (Portunus pelagicus) shell is a marine biowaste produced by seafood industries. Traditionally, crab shells were collected to be converted into animal feed, however many of them are disposed of as industrial waste. A conversion of crab shells into hydroxyapatite is a better option for producing high-value biomaterial. Hydroxyapatite materials can be used as slow-release fertilizer while combining them with traditional fertilizer or as a stand-alone green fertilizer with high phosphatic content. Prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The crab shells then dried under open sun drying for 12 h, followed by 4 h of drying in the electric oven until reaching 9.5 ± 0.12% wet basis moisture content. The dried crab shells were milled into a fine powder using a pilot-size tubular ball mill (rotation speed 84.6 rpm, 1:10 crab shells, and stainless-steel balls ratio) for 4 h [80]. The produced powder was then sieved using woven wire 325 mesh sieve and produced crab-shell powder with 44 µm in sizes.…”
Section: Preparation Of Calcium Oxidementioning
confidence: 99%
“…The crab shells then dried under open sun drying for 12 h, followed by 4 h of drying in the electric oven until reaching 9.5 ± 0.12% wet basis moisture content. The dried crab shells were milled into a fine powder using a pilot-size tubular ball mill (rotation speed 84.6 rpm, 1:10 crab shells, and stainless-steel balls ratio) for 4 h [80]. The produced powder was then sieved using woven wire 325 mesh sieve and produced crab-shell powder with 44 µm in sizes.…”
Section: Preparation Of Calcium Oxidementioning
confidence: 99%
“…In recent times, the dynamic and mechanical assessment of materials have also been studied; for example, Nedaipour et al 12 examined the composition of HAp, polyethylene, glycol and a melt blend of polylactic acid in interference screws; their study analyzed the mechanical and tensile properties of the derived composite relative to material containing pure polylactic acid; the result findings suggest that the derived composite material presents better mechanical properties. Wibisono et al 13 reported the kinetic model for crab shell milling parameters through the use of ball mills. The model tends to reduce the size of the crab shell before HAp conversion.…”
Section: Introductionmentioning
confidence: 99%